Empowerment on healthcare professionals: A literature review - Santos de Carvalho, Carla Maria (2017)
Objectives: To review studies that focus on the influence of structural empowerment in the adoption of mobilizing behaviours and the occurrence of adverse events associated with care. Method: We performed a literature review using specific keywords and applying inclusion/ exclusion criteria. We searched different databases for articles about adverse events, empowerment and mobilization which were published in 1996-2012. We analysed the studies and classified them in terms of empirical/theoretical content, country, sample, measures and results. Results: The literature on this area is extensive, with a majority of empirical studies. Structural empowerment generates positive outcomes at the workplace; these results relate to an increased job satisfaction, an increased organizational commitment, the adoption of innovative behaviours, and a reduction of burnout and turnover. Some articles suggest that empowerment has a positive influence in patient safety, translating into a reduction of adverse events, and in the adoption of mobilizing behaviours by healthcare professionals. Conclusion: A culture of empowerment and mobilization has positive effects in health organizations, and may improve the quality of the patients’ treatment and safety, decreasing the occurrence of adverse events.